DIFFERENCES IN INDEPENDENT LEARNING OF STUDENTS WHO TAKE AND THOSE WHO DO NOT TAKE BIOLOGY TUTORING OUTSIDE SCHOOL - Hici Miyorina; Ardi Ardi; Nini Nezalni (ATRIUM PENDIDIKAN BIOLOGI, 2022)
Students tend to have concerns in carrying out learning to achieve good learning outcomes, so students want to add to their learning outside of school. In the current era of globalization, there have been many tutoring institutions that have developed in various regions in Indonesia. This causes the interest of students to take tutoring outside of school. The purpose of this study was to determine the differences in the learning independence of students between those who take and those who do not take tutoring. This descriptive research was conducted in the even semester of 2019/ 2020 with a population of 266 students. The research sample was students who attended and students who did not take biology tutoring outside of school. The sampling technique used was quota sampling technique, and a sample of 37 people was obtained. The data analysis technique used is the two-average difference test. The results of data analysis showed that the two data were not normally distributed and also not homogeneous, so the U test was used. The test results showed that U count 89.5 while U table 103, in other words U count < U table therefore it can be concluded that there is no significant difference between students' biology learning independence follow with those who do not follow tutoring outside of school.